HUBUNGAN ANTARA KOMPETENSI SOSIAL DENGAN PENYESUAIAN SOSIAL PADA REMAJA - Wardani, Rinanda; -, Apollo (Widya Warta, 2010)
This research aimed to analyze the relation between social competence and social adaptation on youths. Besides, it was also meant to search the difference of social adaptation among  youths (boys and girls). The population of the research was  986 high school students in Kota and Kabupaten Madiun. The sample of the research was 288 students, comprising 125 boys and 163 girls. The data were collected by the use of one scale and one questionnaire namely, social adaptation scale and social competence questionnaire. The data were analyzed  using Product Moment Correlation and T- test. The result of the data analysis showed  that: 1) there was positive and very significant relation between social competence and social adaptation on youths with rxy 0.154, at significance level 0.000 (p < 0.05)  and 2) there was very significant difference of  social adaptation among youths based on sex (boys and girls). Social adaptation level on  t was 5.704 at significance level 0.000 (p < 0.05). Girls had higher social adaptation than boys.